Estońska wizja obrony cywilnej jako istotny element koncepcji bezpieczeństwa całościowego w odpowiedzi na potencjalny kryzys polityczny (Politeja, 2023)
THE ESTONIAN VISION OF CIVIL DEFENCE AS AN IMPORTANT ELEMENT OF OVERALL SECURITY IN RESPONSE TO A POTENTIAL POLITICAL CRISISRussia’s annexation of Crimea in 2014 began the modernisation of state security systems in the Baltic Sea region. A pioneer in the creation of comprehensive security was the Republic of Estonia, which began to implement the total defence strategy as early as 2008, after the political crisis caused by the Russian minority. The protests have disrupted the functioning of Estonian public institutions and the private sector, which are threatened by cyberattacks. The Russian Federation could use not only military but also hybrid means. Therefore, Estonia has decided to implement a completely new version of the total defence strategy. The paper seeks to assess the Estonian concept of holistic security, with particular emphasis on solutions for civil defence in crisis situations.